HUBUNGAN DISIPLIN DENGAN TANGGUNG JAWAB BELAJAR SISWA - Faizatul Lutfia Yasmin; Anang Santoso; Sugeng Utaya (Pascasarjana Universitas Negeri Malang, 2016)
This study aimed to learn discipline and responsibility, as well as how to discipline relations with the responsibilities of student learning. This type of research is descriptive correlation with a quantitative approach. Collecting data using a questionnaire with fourth grade students object Cluster III District of Ngimbang Lamongan. Data were analyzed using Pearson correlation analysis. The results of data analysis known to most students have the discipline and sense of responsibility of higher learning, correlation values obtained Perason rhitung of 0.823 with significance value = 0.000. rtabel with degrees of freedom (df = 90) for α = 0.05 value obtained 0.205. The next step to do a comparison, where the value is greater than rtabel rhitung (0.823> 0.205), and in addition the significant value gained less than α = 0.05 (0.000 <0.05) so that it can be concluded, and there is a relationship of discipline with responsibility learn. Tujuan penelitian mengetahui kedisiplinan dan tanggung jawab belajar, serta bagaimana hubungan disiplin dengan tanggung jawab belajar siswa. Jenis penelitian adalah deskriptif korelasional dengan pendekatan kuantitatif. Pengumpulan data menggunakan angket dengan objek siswa kelas IV SD Gugus III Kecamatan Ngimbang Kabupaten Lamongan. Teknik analisis data menggunakan analisis korelasi pearson. Hasil analisis data diketahui sebagian besar siswa memiliki disiplin dan rasa tanggung jawab belajar tinggi, uji korelasi Perasondidapatkan nilai rhitung sebesar 0,823 dengan nilai Signifikansi = 0,000. rtabel dengan derajat bebas (df=90) untuk α = 0,05 didapatkan nilai 0,205. Langkah selanjutnya dilakukan perbandingan, di mana nilai rhitung lebihbesar daripada rtabel  (0,823 > 0,205), dan selain itu nilai signifikansi yang diperoleh kurang dari α = 0,05 (0,000 < 0,05) sehingga dapat disimpulkanserta terdapat hubungan disiplin dengan tanggung jawab belajar.